2.3 Matroid 101
Theorem 2.3.47 (K¨onig–Egerv´ary theorem for bimatroids). Let
L =(S, T, λ) be a bimatroid with birank function λ. Then there exists
(X, Y ) ∈ 2
S
× 2
T
such that
(i) |X|+ |Y |−λ(X, Y )=|S|+ |T |−λ(S, T ),
(ii) λ(X \{x},Y \{y})=λ(X, Y ), ∀x ∈ X, ∀y ∈ Y .
If min(|S|, |T |) >λ(S, T ), then X = ∅ and Y = ∅.
Proof. Obviously, there exists (X, Y ) satisfying (i) (e.g., X = S, Y = T ). Let
(X, Y ) be such a pair with |X|+ |Y | minimal. Put λ(X, Y
)=a and suppose
that (ii) fails. Then λ(X \{x},Y \{y}) ≤ a − 1 for some x ∈ X, y ∈ Y .The
inequality (B-3) shows
2a − 1 ≥ λ(X, Y )+λ(X \{x},Y \{y}) ≥ λ(X \{x},Y)+λ(X, Y \{y}).
This implies that either λ(X \{x},Y)=a − 1orλ(X, Y \{y})=a − 1.
In the former case, (X \{x},Y) satisfies (i), contradicting the minimality of
|X|+|Y |
. Similarly for the latter case. Therefore, (X, Y ) satisfies (ii). Suppose
that min(|S|, |T |) >λ(S, T ) and either X = ∅ or Y = ∅. Then we would have
|S|+ |T |−λ(S, T ) > max(|S|, |T |) ≥ max(|X|, |Y |)=|X| + |Y |−λ(X, Y ), a
contradiction to (i).
A canonical choice of the pair (X, Y ) in Theorem 2.3.47 can be made by
way of the canonical partition of a bimatroid introduced by Geelen [92]. For
a bimatroid L =(S, T, λ)andZ ⊆ S ∪ T , we denote by L \ Z the bimatroid
with Z deleted, i.e., L \ Z =(S \ Z, T \ Z, λ
) with λ
(X, Y )=λ(X, Y )for
X ⊆ S \ Z and Y ⊆ T \ Z. Define a partition of S ∪ T into three disjoint
parts by
D(L)={z ∈ S ∪T | rank (L \{z})=rankL},
A(L)={z ∈ S ∪T | D(L \{z})=D(L)},
C(L)=(S ∪T ) \ (D(L) ∪ A(L)).
The partition (D(L),A(L),C(L)) is called the
canonical partition of L.
The canonical partition enjoys the following nice properties (Geelen [92]).
Proposition 2.3.48. For x ∈ S \ D(L) the following hold true.
(1) D(L \{x}) ∩ S = D(L) ∩ S.
(2) D(L \{x}) ∩ T ⊇ D(L) ∩ T .
(3) If y ∈ D(L \{x}) \ D(L), then x ∈ D(L \{y}).
(4) A(L \{x}) ∩ T ⊆ A(L) ∩ T .
Proof. (1) Note the relation S \
D(L)={coloops of RM(L)} as well as
the similar relation for L \{x}. Since x is a coloop of RM(L), we have
{coloops of RM(L)} = {x}∪{coloops of RM(L \{x})}.
(2) For y ∈ D(L) ∩ T we have rank (L \{x, y}) = rank (L \{x}), since
λ(S \{x},T) ≥ λ(S \{x},T \{y}) ≥ λ(S \{x},T)+λ(S, T \{y})
−λ(S, T )
by (B-2) and (B-3), and λ(S, T )=rankL = λ(S, T \{y}).